The Influence of The TASC (Thingking Actively In A Social Context) Model Using Whatsapp Social Media on Online Learning Materials for Classification of Land Capability in the Emergency Period of the Covid 19 Pandemic - Rosikh Musabikha M; Miftahul Khair Abdul Muqsith; Muaris Maulana (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
This study aims to determine the effect of the Tasc model using WhatsApp social media on online learning for Land Capability Classification Analysis during the COVID-19 pandemic emergency. The method used in this study is an experimental method with a quasi-experimental type using a factorial design. The samples in this study were students of class X IPS 1 and class X IPS 2. The results of this study were analyzed in stages, namely: data description, prerequisite test, and hypothesis testing. The prerequisite tests carried out are the normality test of the data distribution, the homogeneity of variance test, and the t test. The results showed that after the learning was carried out and the post-test was given to the experimental class and the control class, the results obtained ttest > t ???????????????????? indicating was accepted . Where that the learning outcomes of students on the material elements of hadith using the TASC learning model are better than conventional learning. Where the class that uses the TASC model seems enthusiastic about sending information on the Whatsapp group because the TASC learning model helps students to construct their own knowledge and makes it easier for students to understand the classification of land capability.